EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE BERBASIS ASSESSMENT FOR LEARNING PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KREATIVITAS SISWA KELAS VIII SMP NEGERI SE-KABUPATEN PONOROGOTAHUN 2013/2014 - Dwi A, Yuridis Madyarsa; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research was aimed to know in polyhedral concept: (1) which one give better achievement between TPS-AfL, TPS, or Direct Learning, (2) which one have better achievement between high, medium or low creativity students, (3) for each creativity levels, which one give better achievement between TPS-AfL, TPS, or Direct Learning, (4) for each learning model, which one have better achievement between high, medium or low creativity students. This was quasi-experimental research designed by factorial 3x3. The population was 8th grade students of SMPN even semester academic year 2013/2014 in Ponorogo regency. The sample was taken by using stratified cluster random sampling. Total sample was 255 students, consisted of 79 students as TPS-AfL sampel, 89 students as TPS sampel, and 87 students as Direct Learning sampel. The data were collected by using documentation, questionnaire and test. The data of research were analyzed by using analysis of variance with unequal cells, then continued by using Scheefe? method. According to the data analysis, it can be concluded that in polyhedral concept: (1) students learnt using TPS-AfL and TPS, had better achievement than students learnt using Direct Learning, students learnt using TPS-AfL had better achievement than students learnt using TPS, (2) high creativity students had better achievement than those of medium and low creativity students, however medium and low creativity students had the same achievement, (3) for TPS-AfL and TPS learning, students with high, medium, and low creativity had the same achievement, for Direct Learning, high creativity students had the same achievement as medium creativity students, however medium creativity students had the same achievement as low creativity students, meanwhile high creativity students had better achievement than low creativity students, (4) for high and medium creativity students, TPS-AfL, TPS, and Direct Learning gave the same achievement, meanwhile for low creativity students, TPS-AfL gave better achievement than students TPS and Direct Learning, meanwhile, TPS and Direct Learning gave the same achievement.Keywords: TPS-AfL, TPS, Direct Learning, Creativity